Impact of Quality Improvement Bundle on Compliance with Resuscitation Guidelines during In-Hospital Cardiac Arrest in Children - Pranali Awadhare; Karma Barot; Ingrid Frydson; Niveditha Balakumar; Donna Doerr; Utpal Bhalala (Critical Care Research and Practice)
Introduction. Various quality improvement (QI) interventions have been individually assessed for the quality of cardiopulmonary resuscitation (CPR). We aimed to assess the QI bundle (hands-on training and debriefing) for the quality of CPR in our children’s hospital. We hypothesized that the QI bundle improves the quality of CPR in hospitalized children. Methods. We initiated a QI bundle (hands-on training and debriefing) in August 2017. We conducted a before-after analysis comparing the CPR quality during July 2013–May 2017 (before) and January 2018–December 2020 (after). We collected data from the critical events logbook on CPR duration, chest compressions (CC) rate, ventilation rate (VR), the timing of first dose of epinephrine, blood pressure (BP), end-tidal CO2 (EtCO2), and vital signs monitoring during CPR. We performed univariate analysis and presented data as the median interquartile range (IQR) and in percentage as appropriate. Results. We compared data from 58 CPR events versus 41 CPR events before and after QI bundle implementation, respectively. The median (IQR) CPR duration for the pre- and post-QI bundle was 5 (1–13) minutes and 3 minutes (1.25–10), and the timing of the first dose of epinephrine was 2 (1-2) minutes and 2 minutes (1–5), respectively. We observed an improvement in compliance with the CC rate (100–120 per minute) from 72% events before versus 100% events after QI bundle implementation (p=0.0009). Similarly, there was a decrease in CC interruptions and hyperventilation rates from 100% to 50% (p=0.016) and 100% vs. 63% (p=<0.0001) events before vs. after QI bundle implementation, respectively. We also observed improvement in BP monitoring from 36% before versus 60% after QI bundle (p=0.014). Conclusion. Our QI bundle (hands-on training and debriefing) was associated with improved compliance with high-quality CPR in children.